Essential Oil of Lippia origanoides (Verbenaceae) in cleaning of teats dairy cows (Research, Society and Development, 2021)
The present study aimed with the objective evaluate the effectiveness of a new product made with essential oil of pepper rosemary under the reduction of the count of microorganisms present in the skin of teats of dairy cows. For the in vivo test, the effectiveness of the new product under negative antisepsis for clinical mastitis (192 teats), was evaluated in comparison with the treatment containing commercial products (192 teats), in a period of 42 days. The teats were monitored clinically daily, with a weekly assessment of the microbiota present on their skin as to a reduction in the count of Staphylococcus aureus, coagulase negative staphylococci (SNC), Echerichia coli and mesophilic aerobes. Both products maintained the integrity of the teats, with the absence of clinical mastitis observed during the experimental period. There was no significant difference in the occurrence of subclinical mastitis and microorganisms on the teats of the two groups under study by Fisher’s test at a significance level of 5%. When companing the log reduction of the count in UFC.mL-1 of the microorganisms for the group treated with conventional product and with experimental product for aerobic mesophiles, E. coli, S. aureus and coagulase negative staphylococci, observed with the cleaning process of the teats, a Statistical difference was observed (p>0,05), in the counting of microorganisms, showing that both effect similar to the control of microorganisms present in the skin of the teats. Thus, the new product containing essential oil of pepper rosemary showed similar efficacy to the convencional product chlorhexidine and iodine for antisepsis of dairy cow teats without promoting local reactions on the skin, and can be used as an alternative product in the handling of milking.